전공기반의 신입생세미나 운영 효과 검증―상담심리학과 신입생을 대상으로 - 권해수 (교양교육연구, 7(2), 2013)
본 연구는 전공기반의 신입생세미나 교육내용을 개발하고 실제 운영을 통하여 그 효과를 검증하는 데 목적이 있다. 이를 위해 본 연구는 다음 세 단계로 진행되었다. 첫째, 신입생 교육에서 효과가 검증된 교육내용 및 운영방법과 신입생 욕구조사 결과를 토대로 신입생세미나 교육내용을 개발하였다. 둘째, C대학 상담심리학과 1학년 10명을 대상으로 2시간 30분씩, 총 9주에 걸쳐 신입생세미나를 운영하였다. 셋째, 대학생활적응 척도와 자기효능감 척도의 사전·사후 측정과 참여자 심층 인터뷰를 통하여 신입생세미나 운영 효과를 분석하였다. 연구 결과, 전공기반의 신입생세미나 교양교육이 신입생의 대학생활 적응, 전공 정체성 확립, 진로 설계 및 자기 효능감 증진에 긍정적인 영향을 미치는 것으로 나타났다. 마지막으로 본 연구의 제한점 및 신입생세미나 활성화 방안을 제언하였다. The purpose of this study was to analyze the effects of operating college freshmen seminar after its newly development on the major basis. For this purpose, three stages were taken as follows. First, literature was reviewed to find out what the effective factors was used in developing and operating new curriculums. What freshmen needed were explored through the 'wanting' survey, and new curriculums of freshmen seminar was developed by the researcher. Second, The freshmen seminar was run every week for 2 and half hours for 9 weeks to freshmen students from Department of Counseling Psychology. Third, operating effect of freshmen seminar was explored through pre- and post-test to measure the students' adaptation for college life and self-efficacy scale quantitatively with the in-depth interviews qualitatively. The results indicated that freshmen seminar was effective to elevate their adaptability for college life, to develop a sense of solidarity to majors, and to promote self-efficacy. Finally, the limitation of this study and future study direction were discussed. KCI Citation Count: 21